PENGARUH METODE PEMBELAJARAN INKUIRI TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Yudi Saputra; Pramudiyanti Pramudiyanti; Berti Yolida (Universitas Lampung, 2014)
This research aimed to know the influence of guided inquiry learning methods towards student’s learning activities and student’s learning result. The design of this research was pretest-posttest with non equivalent. The subject of this research was student in the class VIIA and VIIB, chosen by cluster random sampling. This research used qualitative and quantitative data. The qualitative data was the observation sheet of learning activities. The quantitative data was obtained from research of learning and analyzed statistically by t-test. The activities of student’s cooperative in all observed aspects had moderate level that was 77,69 %. The result showed that inquiry learning methods improves student’s achievement in experiment class by average N-Gain about 56,83. Thus, guided inquiry learning methods could increase student’s learning activities and student’s learning result on the subject the characteristic of organisms. Penelitian ini bertujuan mengetahui pengaruh metode pembelajaran inkuiri terbimbing terhadap aktivitas dan hasil belajar siswa. Desain yang digunakan yaitu pretes-postes tak ekuivalen. Subjek penelitian adalah siswa kelas VIIA dan VIIB dipilih secara cluster random sampling. Data penelitian berupa data kualitatif dan kuantitatif. Data kualitatif berupa lembar observasi aktivitas belajar. Data kuantitatif berupa hasil belajar dan dianalisis secara statistik melalui uji-t. Aktivitas belajar siswa dari semua aspek yang diamati berkeriteria baik yaitu 77,69%. Hasil belajar menunjukkan bahwa penggunaan metode pembelajaran inkuiri terbimbing meningkatkan hasil belajar siswa pada kelas eksperimen dengan rata-rata N-gain 56,83. Dengan demikian, penggunaan metode pembelajaran inkuiri terbimbing dapat meningkatkan aktivitas dan hasil belajar siswa pada materi pokok ciri-ciri makhluk hidup. Kata kunci : aktivitas, hasil belajar, metode inkuiri terbimbing